PELATIHAN PEMBUATAN DAN PEMENTASAN SEDERHANA WAYANG GODHONK BERBAHAN LIMBAH DAUN KERING SEBAGAI UPAYA PENINGKATAN PENGETAHUAN SENI BUDAYA BAGI ANAK USIA DINI DI SANGGAR SENI MIJILAN, DUSUN PRINGAPUS, KALISALAK, SALAMAN, MAGELANG - Dr. Agus Purwantoro,M.Sn (Institut Seni Indonesia Surakarta, 2021)
Abstract Early childhood (PAUD-TK) is considered a sensitive period or sensitive period in children, namely a period where certain functions need to be stimulated physically-motor, intellectual, social, and emotional. This form of stimulation is in the form of education and teaching for families, communities, and schools. The effort also aims to raise the character of students, namely the subtlety of feelings (morals), which will then produce intelligence of the mind, and produce will power. To educate these feelings, Ki Hadjar Dewantara said that there are 2 things that must be passed, firstly, education on the subtleties of spiritual life which is called moral education and the second is aesthetic education. Wayang by Ki Hadjar Dewantara is included as an aesthetic education that can smooth the feeling of beauty towards all external objects. Wayang is an ancestral heritage that is rich in artistic and cultural meaning that deserves to be introduced to early childhood. This is the case with Wayang Godhong. The puppets, which are made from godhong (leaves) of teak and coffee, are the fruit of Gus Pur's ideas and should be introduced to children from an early age. The hope is that they will get to know the unique Wayang Godhong as a medium that will bring them closer to art and culture and their love for nature. Through the service that will be carried out in Magelang Regency, precisely in the Mijilan Art Studio, Pringapus Hamlet, Kalisalak, Salaman, Magelang. children will be invited to see the manufacturing process, practice making with dry leaf waste, and perform it in a simple way.